Support needs and satisfaction in kinship foster care - Bernedo Muñoz, Isabel Mª; Fuentes Rebollo, María Jesús (Anales de Psicología / Annals of Psychology, 2010)
Research shows that on kinship foster care the caregivers re-ceive less support, than other kind of foster care. This research analysed 54 grandparents with custody of their grandchildren to determine what support they were receiving. The mean age was 65.9 for the grandfathers and 63.6 for grandmother. In total, they were caring for 70 adolescents with a mean age of 14 years old, ranging between 11 and 17. The ques-tionnaire was filled in by grandparents in their homes. The aim research is to know social, economic and emotional support received and expressed by grandparents, and to know the satisfaction with the foster care in rela-tion with support received. The results show what little support the grandparents receive. The grandparents expressed a need for more eco-nomic support and more information about the foster care process, but not more professional supervision after foster care. The grandparents also stated that they have support from both family and friends. Furthermore, grandparents expressed high satisfaction with care their grandchildren. This satisfaction was in relation with support received.